2007
DOI: 10.1111/j.1365-2222.2007.02884.x
|View full text |Cite
|
Sign up to set email alerts
|

Ovalbumin‐sensitized mice are good models for airway hyperresponsiveness but not acute physiological responses to allergen inhalation

Abstract: The lack of an LPR, limited EPR and the absence of a link between the LPR and AHR highlight the limitations of this mouse model as a complete model of the lung dysfunction associated with asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 43 publications
3
51
0
3
Order By: Relevance
“…findings correlate well with the asthma model reported by Zosky et al [29] . Sera from KO mice showed a similar level of IgE and a higher level of IgG1 compared to WT mice.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…findings correlate well with the asthma model reported by Zosky et al [29] . Sera from KO mice showed a similar level of IgE and a higher level of IgG1 compared to WT mice.…”
Section: Discussionsupporting
confidence: 82%
“…It was reported that OVA-sensitized mice are good models for airway hyperresponsiveness, but not for acute response to inhaled allergen after OVA challenge because of limited EPR and LPR in BALB/c mice [29] . In our study, airway hyperresponsiveness to MCh was successfully induced in both KO and WT mice, with the extent of increase significantly larger in KO mice than in WT mice.…”
Section: Discussionmentioning
confidence: 99%
“…The dependence of most of the components of this response, including AHR, on STAT6 signaling is not surprising, considering the strong connection between STAT6 and AHR and the Th2-associated airway inflammation that has been found in multiple studies of allergic asthma (32)(33)(34). The association of the inflammatory response we describe here in BALB/c mice with STAT6 is more complex than a simple Th2 differentiation decision.…”
Section: Discussionmentioning
confidence: 74%
“…First, species differences may be responsible; BBS might increase the risk for asthma in humans but not in mice. Although the ovalbumin sensitization model is widely used in asthma research, it is not identical to human asthma (40). Second, perhaps loss of BBS does predispose to ''asthma'' in mice, but the tests we used were not sufficiently sensitive to detect it.…”
Section: Discussionmentioning
confidence: 99%